2019
DOI: 10.3390/molecules24183274
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Pien-Tze-Huang: A Review on Its Chemical Composition, Pharmacology, and Clinical Application

Abstract: Pien-Tze-Huang (PTH) is a famous and commonly used traditional Chinese medicine formula in China. It was first formulated by a royal physician of the Ming Dynasty (around 1555 AD). Recently, PTH has attracted attention worldwide due to its beneficial effects against various diseases, especially cancer. This paper systematically reviewed the up-to-date information on its chemical composition, pharmacology, and clinical application. A range of chemical compounds, mainly ginsenosides and bile acids, have been ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 50 publications
(69 reference statements)
0
16
0
Order By: Relevance
“…By searching TCM Database@Taiwan ( http://tcm.cmu.edu.tw/ ), TCMSP ( http://tcmspw.com/tcmsp.php ), and related literature, we collected the main chemical components of Calculus Bovis, Moschus, Rhizoma Notoginseng , and Snake Gall in PTH, respectively. The oral bioavailability (OB ≥ 30%), drug-likeness (DS ≥ 0.18), and clear biological activity report [ 13 , 27 ] were employed to identify the possible bioactive compounds in PTH. 2D and 3D structures and structural graphics of the above compounds were obtained using the PubChem database ( https://pubchem.ncbi.nlm.nih.gov/ ) and saved in mol2 format.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By searching TCM Database@Taiwan ( http://tcm.cmu.edu.tw/ ), TCMSP ( http://tcmspw.com/tcmsp.php ), and related literature, we collected the main chemical components of Calculus Bovis, Moschus, Rhizoma Notoginseng , and Snake Gall in PTH, respectively. The oral bioavailability (OB ≥ 30%), drug-likeness (DS ≥ 0.18), and clear biological activity report [ 13 , 27 ] were employed to identify the possible bioactive compounds in PTH. 2D and 3D structures and structural graphics of the above compounds were obtained using the PubChem database ( https://pubchem.ncbi.nlm.nih.gov/ ) and saved in mol2 format.…”
Section: Methodsmentioning
confidence: 99%
“…PTH has a history of more than 500 years and has been used as a folk medicine in China and Southeast Asia to treat various inflammation-related diseases such as hepatitis. In China, PTH is clinically used to protect the liver [ 11 , 12 ], treat hepatitis [ 13 ], improve liver fibrosis [ 14 ], and treat liver cancer [ 15 – 17 ]. Studies on the effects of PTH on lung cancer [ 18 ], intestinal cancer [ 19 , 20 ], osteosarcoma [ 21 ], and liver cancer [ 22 ] have been reported, but the active ingredients of PTH on liver cancer and the relevant molecular mechanisms are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Panax notoginseng roots PZH is composed of four TCM ingredients, including Radix et Rhizoma Notoginseng (85%), Moschus (3%), Calculus Bovis (5%), and Snake Gall (7%) [17][18][19]. Panax notoginseng (P. notoginseng), also known as Chinese ginseng, is distributed primarily in southwest China, mainly due to its peculiar growth habitat.…”
Section: Major Active Componentsmentioning
confidence: 99%
“…Studies have found that PZH has the functions of clearing away heat and detoxification, reducing swelling and relieving pain, anti-inflammatory effects, and liver protection [21][22][23]. Clinically, it is widely used in various inflammatory diseases, such as viral hepatitis, alcoholic hepatitis, and fatty liver [24]. Currently, the mechanism of PZH in ALD remains unclear.…”
Section: Introductionmentioning
confidence: 99%